Bank power and public policy since the financial crisis. (March 2020) - Macartney, Huw; Howarth, David; James, Scott
Abstract: Despite much commentary in the media and the popular assumption that the banking industry exerts undue influence on government policy-making, the academic literature on the role of the banks since the 2008 financial crisis remains theoretically and empirically under-specified. In particular, we argue that different forms of financial power are often conflated, while favorable policy outcomes are too-readily assumed to be evidence of regulatory capture. In short, we still know relatively little about how bank influence varies over time and in different national contexts, the extent to which banking interests are unified or divided, and the conditions under which banks are capable of producing meaningful variation in policy outcomes. This article has three objectives: 1) to explain why the debate on bank influence matters; 2) to examine the evidence of bank influence since the international financial crisis; and 3) to set out a range of conceptual tools for thinking about bank power.